KONFLIK PENGUASAAN TANAH PERKEBUNAN - HERAWAN SAUNI (Universitas Bengkulu, 2016)
Abstract There is a vivid imbalance in farm land domination. This emerge conflict in almost Indonesia territory. Structuring the ownership or control of land has been started since the Act Numebr 5 of 1960 as the reference in the structuring of the agricultural land holdings in Indonesia. However, what is hoped and be the justification reason the act seems has not shown as demanded. Based on Decree of Head of BPN RI Number 34 of 2007 on Technical Guidelines for Handling and Resolution of Land Issues, land conflicts arise regarding the issue of tenure, ownership, use or utilization of the plot of land. The enactment of Law No. 18 of 2004 on Plantations also open conflicts between farmers and plantation companies. Conflict occurs when the plantation is difference between one or more people or groups of people with plantation companies relating to land tenure estates. There are several factors that cause conflict, especially agricultural land tenure plantation land, namely: (1) inequality of agricultural land holdings; (2) there is a vagueness setting land rights; (3) wasteland physically; and (4) overlapping land ownership. Recalling the complexity of the conflict over land, land conflict resolution should be based not only on purely formal legal approach but also through other approaches such as economic, social and cultural.